CHRISTIAN FORGIVENESS, RECONCILIATION, AND CONGREGATIONAL LIFE: QUANTITATIVE EVIDENCE FROM GMIM CHURCHES IN INDONESIA - Valdo Vreden Woruntu; Evi Stans Evlin Tumiwa; Olga Neltje Komaling; Sekry Evan Sandiata (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This paper reports a quantitative research on CM Christian forgiveness, reconciliation, and life in GMIM churches in Indonesia. This study examines the actualization of theological beliefs regarding forgiveness in daily relationships using a cross-sectional survey of adult members of various congregations and their role in the vitality of congregations. The concept of forgiveness is heavily asserted as a non-negotiable Christian ministry, and it is commonly experienced as peace in the soul. Respondents associated the forgiveness of other people with obedience to God and the release of anger and bitterness, and they considered other spiritual practices, such as prayer, to be relevant supports towards release. Simultaneously, the participants have a reticent and discriminating attitude: they note that they find it more demanding to forgive serious or recurrent crimes, and they always distinguish between intrapersonal forgiveness and interpersonal reconciliation. It is typically considered that reconciliation would only be acceptable where there is repentance, change of behavior, and relational safety, and in most cases under the mediation of pastors or elders. The sense of congregational climate indicates that teaching forgiveness is perceived to be consistent and clear, and practices of conflict handling and leadership modelling are perceived to be uneven. The patterns of correlation show that a better sense of belonging, perceived unity, and active engagement in ministries are linked to stronger forgiveness and reconciliation orientations. This study concludes that forgiveness and reconciliation are not just theological principles but also practical sources of congregational well-being and valuable tools in Christian witness in a plural and postcolonial society.